Agriculture, the Structural Funds and the Budget after Enlargement - Jim Rollo (Romanian Journal of European Affairs, 2004)
The purpose of this article is to examine how the legacy of the, often bruising, negotiations at Copenhagen and subsequently over agriculture will affect the political economy of the European Union and specifically the challenges facing the CAP, the Structural Funds in the next decade. The EU Budget for the remainder of the 2000-2006 Framework was fixed by the EU-15 at the Brussels Summit of October 2002 (European Council, 2002b) and is very unlikely to change. That is why the first real battle over resources engaging the new members will turn out to be the Financial Framework post 2006. This article will discuss the general context, before examining agriculture policy and structural funds after Copenhagen summit and finally the implications for the next Financial Framework.